2022
DOI: 10.21203/rs.3.rs-1353931/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phytochemical composition, antibacterial and antioxidant activities of the ethanolic root extract of the endemic Onosma, northern Iran.

Abstract: This experimental study was performed for determining the antioxidant and antibacterial bioactivity of Onosma dichroantha’s root extract obtained using ethanol as our solvent. The results showed that phthalic acid, di(2-propylpentyl) ester (54.52%), .beta.-sitosterol (16.65%) and ethanol, 2-(butylamino)- (13.32%) were the major compounds of the ethanolic root extract of O. dichroantha. Total phenols was determined by the Folin-ciocalteu method and the flavonoid content was determined by the colorimetric alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Therefore, it can be concluded that the formation and growth of CaOx crystal is prevented by the antioxidant properties of these compounds. In addition, compounds such as, thiophene, thiazole, and phthalic acid, di (2-propylpentyl) ester have anti-inflammatory properties (Lemilemu et al, 2021;Mishra et al, 2022;Pahlavan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be concluded that the formation and growth of CaOx crystal is prevented by the antioxidant properties of these compounds. In addition, compounds such as, thiophene, thiazole, and phthalic acid, di (2-propylpentyl) ester have anti-inflammatory properties (Lemilemu et al, 2021;Mishra et al, 2022;Pahlavan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be concluded that the formation and growth of CaOx crystal is prevented by the antioxidant properties of these compounds. In addition, compounds such as, thiophene, thiazole, and phthalic acid, di (2‐propylpentyl) ester have anti‐inflammatory properties (Lemilemu et al, 2021; Mishra et al, 2022; Pahlavan et al, 2022). High oxalate and CaOx crystals can induce inflammatory response through the activation of NLR family pyrin domain containing 3 (NLRP3) inflammasome, which triggers the release of proinflammatory cytokines IL‐1β and IL‐18.…”
Section: Discussionmentioning
confidence: 99%
“…Medicinal plants are effective in treating infectious disorders and infections of many types of external wounds [42][43][44] . The antibacterial activity of the ethanolic root extract of O. dichroantha was investigated by Pahlavan et al 45 by utilizing the disk diffusion method. The results showed that the extract had high bioactivity at 100 mg/mL, with zones of inhibition ranging from 6.0 ± 0.00 to 16.3 ± 1.52 mm on Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus pneumoniae, Streptococcus agalactiae, Enterococcus faecalis, Escherichia coli, Shigella sonnie, Shigella flexteriae, Listeria monocytogenes, Staphylococcus epidermis and Streptococcus pyogenes.…”
Section: Ffmentioning
confidence: 99%